Implications and Requirements for Implementing Corporate Governance as an Institutional Advantage for the Value Chain of the Costa Rican Cooperative Sector (National Administration Journal, 2023)
Corporate governance was born before the Wall Street crisis, creating the need for decision makers to respond to shareholders for their business practices, thus a qualitative study was prepared on the Costa Rican cooperative sector through an expert sampling on the predominant factors for the implementation of corporate governance and that through the achievable methodological alternative, proposed by Pablo Cáceres, it was detected that there is an optional differentiation of the Costa Rican legislator to supervise the monetary controls of cooperatives, which implies a disadvantage in terms of the presence of a robust and up-to-date regulatory and oversight structure.
Keywords: Corporate governance; cooperative sector; financial markets; corporate governance code and organization for economic cooperation and development (OECD)